ISOLATION INCIDENCE AND CHARACTERISTICS OF THE BACTERIOPHAGE OF R MELILOTI - SANCHEZ MARROQUIN, AY; CASAS CAMPILLO, CARLOS (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Because the great importance of the glycogenic function of the hepatic cell, the author accepts as more accurate, the tests that deal with the metabolism of glycids, specially the Althausen test, based on the detn of glycemia before meals and after the a
AN ESC NAC CIENC BIOL
Keywords: ISOLATION, INCIDENCE, CHARACTERISTICS, BACTERIOPHAGE, R MELILOTI; CIENCIAS DE LA VIDA; MICROBIOLOGIA; BACTERIOFAGOS